Phyllanthus niruri reduces renal azotaemia in rats induced with chronic renal failure - Hamzah, Hazilawati; P., Farah Dina; Shaari, Mohd Rosly; Sithambaram, Shanmugavelu; Mohamed Mustapha, Noordin (Malaysian Medical Association, 2010)
Phyllanthus niruri is commonly used for treatment of jaundice, hepatitis, kidney stones, diuretics, influenza and antibacterial agent. This study was conducted to investigate the effects of P. niruri in reducing the severity of azotaemia in rats induced with chronic renal damage. A total of 32 male Sprague Dawley rats were randomly assigned into four treatment groups; Group A (control), Group B (adenine), Group C (P. niruri) and Group D (adenine+P. niruri), consisting of 8 rats each. Chronic renal damage was induced using 0.75% adenine mixed with rat diet (daily feeding for 6 weeks). P. niruri was supplemented daily at a dose of 3000 mg/kg body weight throughout the 10 weeks of the experimental period. Results showed that P. niruri reduced the severity of azotaemia in rats induced with chronic renal damage.